Bifunctional catalysts composed of low silicon‐content SAPO‐34 nanosheets and In2O3/ZrO2 with improved performance for CO2 hydrogenation. Issue 2 (7th April 2022) - Liu, Zichen; Xu, Shuman; Hao, Jing; Song, Lina; Chong, Mingben; Cheng, Dang‐Guo; Chen, Fengqiu
Abstract: The conversion of CO2 into high‐value chemicals has drawn a great deal of consideration, of which the most ideal product is lower olefins. However, the modified Fischer–Tropsch (F‐T) synthesis with CO as an intermediate shows poor selectivity for lower olefins. Here, a list of bifunctional catalysts consisting of SAPO‐34 zeolites with adjustable silicon contents and In2 O3 /ZrO2 were synthesized. In the reaction process, CO2 is first hydrogenated to methanol over an In2 O3 /ZrO2 catalyst, and then the generated methanol rapidly diffuses to the adjacent zeolite catalyst to react to lower olefins. The selectivity of lower olefins (88.3%) and conversion rate of CO2 (23.3%) was achieved over In2 O3 /ZrO2 and SAPO‐34‐0.05 at 633 K, a gas hourly space velocity (GHSV) of 4500 ml·gcat –1 ·h –1, and H2 /CO2 /Ar = 3:1:1. The catalytic performance remained stable after 50 h of reaction. Characterization analysis showed that Si content affected the content of Brønsted acid sites (BAS) and morphology of SAPO‐34, resulting in different distribution of reaction intermediates. Tetramethyl‐benzenes, as important intermediate species, had a slower conversion rate on the SAPO‐34 with low Si content and nanosheet morphology, which led to high lower olefins selectivity. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.